Housing Transformation Review: A Case Study of Low Medium Cost Settlement - Koesmeri, D.R, Ibrahim, S.H., Abdullah, N.A., Wahid, J.,; W.B, Enggu,; M.N.M, Nawi, (Opción, 1970)
Good quality housing is a key element for ensuring a healthy environment. A good house design produces a favorable and comfortable environment. In a hot-humid climate country like Malaysia, the indoor environment often faces issue on heat gain reduction in building spaces due to the commonly increase in high air temperature, relative humidity and low air movement. This leads to thermal discomfort of building occupants. Thus, housing transformation, more often than not is done in order to improve the housing condition and to fulfill the needs of household. This paper discusses the factors influencing transformation and the implications of the transformation activities ensuing spatial qualities. A study was conducted at Taman Sourabaya Indah, Kuching. As a result, 18% of the residents still keep the original design of their houses, while 57% and 25% of houses had gone through horizontal and full transformation respectively. These transformations were done based on physical, social and economic factors. The study concludes that housing transformation occurs to be one of the means for the people especially from low or low medium income earners who strive to get access to housing supply. The intention for a house transformation comes from the residents’ desire to improve their dwelling place, taking into account the physical characteristics of the building in which they live but the ensuing changes can be assumed to have far reaching socio-economic implications.